"I Don't See Myself as Prison Material": Motivations for Entering a Rural Drug Court. (October 2015) - Patten, Ryan; Messer, Sarah; Candela, Kimberlee
Since the inception of drug court in the late 1980s, it has become a widely used alternative to incarcerating drug offenders. Previous research has detailed the effectiveness of programming on recidivism, participants' perceptions of the service delivery model, and cost-effectiveness. The scholarship related to drug offender motivations to participate in drug court has largely discussed family obligations and the sense of loss stemming from drug abuse, and only two studies have discussed the fear of prison as a primary motivator. This research utilized semi-structured interviews with former drug court participants from a rural county in California to ascertain their motivation for engaging in drug court ( N = 29). The results show 79% of participants were trying to avoid prison or jail, while 62% were motivated to end the cycle of drug abuse in their lives. The conclusion has policy implications for future drug court design; however, additional research is needed.